Thermodynamic assessment of the different steps observed during SiC oxidation. Issue 4 (April 2022) - Chatillon, C.; Teyssandier, F.
Abstract: Oxidation studies of SiC are reviewed and analyzed in terms of thermodynamics by crossing the high temperature behavior of the SiC material - mainly the activities of its components during the vaporization processes - with the gas flows supplied to its surface. Additional information is gathered from the abundant literature dealing with surface characterizations using specific instruments in order to elucidate the main chemical surface and interface mechanisms and the associated reactions involved in active and passive oxidation as well as for active-passive or passive-active transitions. Experimental data - erosion rate, growth rate of silica layers and active-passive transition - are discussed in relation with the simulation of equilibrium processes based on thermodynamics.